Optimizing Digital Marketing Strategies to Increase Coffee Tourism Competitiveness in a Sustainable Economy - Muazziss Najmi; Rahma Dani; Fazqiya; Syafridha Yanti (LP2M IAIN Palopo, 2025)
This study aims to analyze digital marketing strategies to enhance the competitiveness of coffee tourism as part of sustainable economic development. Tourism based on local commodities, particularly coffee, has great potential to boost community welfare because it integrates aspects of agriculture, culture, and the creative economy. Coffee is not merely a consumer product but also a cultural identity that can be packaged as a tourist attraction through educational activities, agrotourism, and experience-based tourism. However, limited technology utilization and suboptimal digital marketing strategies remain major obstacles to coffee tourism development. Data collection techniques were conducted through in-depth interviews with managers, field observations, documentation of promotional activities, and literature studies supporting the analysis of digital marketing theory. The results show that optimizing digital marketing strategies can be done through consistent use of social media, strengthening branding based on positioning and uniqueness, and involving local communities in developing promotional content. Social media, such as Instagram, Facebook, and TikTok, have proven effective in building visual narratives about the uniqueness of coffee tourism, while branding that emphasizes the quality of Gayo coffee and the authenticity of the experience is able to attract tourists within a more specific market segment. Furthermore, the involvement of local communities in digital marketing strategies serves not only as promoters but also as cultural agents that maintain the authenticity of the tourism experience. This involvement strengthens the image of coffee tourism as an inclusive, participatory, and sustainable destination. The positive impact of implementing this strategy is not only seen in the increase in tourist visits but also in the opening of new business opportunities for the local community, ranging from homestay management and local transportation to creative coffee-based products. This aligns with the concept of a sustainable economy, where economic benefits are felt not only by business owners but also by the local community as a whole. Therefore, the results of this study confirm that digital marketing strategies play a crucial role in strengthening the competitiveness of coffee tourism, both locally, nationally, and internationally. Successfully utilizing digital technology for promotion not only provides short-term benefits in the form of increased tourism but also encourages the creation of a more sustainable tourism ecosystem. Coffee tourism can develop as a commodity-based tourism model that maintains a balance between economic, social, and environmental aspects, while strengthening regional identity amidst increasingly fierce global competition.